Cost-based optimum design of the earthquake-resistant system for continuous skew overpasses. (November 2022) - Zhang, Penghui; Yuan, Wancheng; Wang, Zhiqiang; Qu, Hongya
Abstract: This study proposes an efficient optimization framework for the earthquake-resistance system of continuous skew overpasses based on a cost-related objective function. The cable-sliding modular expansion joint (CMEJ) was considered to mitigate the rotational response of skew bridges. The BOX-COX regression was used to modify the probabilistic seismic demand model (PSDM) so that assumptions of the cloud method, viz. linearity, normality, and homoscedasticity, can be satisfied. The optimal intensity measure (IM) was selected from ten candidates. Next, the size of laminated rubber bearings (LRBs) and the initial free movement displacement of joints were optimized through the response surface method (RSM) and the Particle Swarm Optimization (PSO). Finally, the proposed framework was demonstrated using a typical three-span skew continuous overpass bridge. The seismic mitigation effectiveness of the CMEJ was discussed, considering the impact of the skew angle. Results indicate that the proposed optimization method can efficiently minimize the cost-related objective function with acceptable accuracy. Additionally, compared to the bridge equipped with modular expansion joints (MEJs), bearings of the bridge equipped with CMEJs have a smaller damage probability while the damage probability of abutments increases, which results in the total expected repair cost decreases obviously. It is also notable that the total expected repair cost of the bridge with MEJs increases as the skew angle becomes more extensive, while the one for the bridge with CMEJs is independent of the skew angle.